Contribution Of Shaligram Nighantu In Dravyaguna Vigyana W.S.R. Vishahar Dravyas - Sharma, Ashwini Kumar; Imtiyaj, Mohd; Soni, Pradeep; Vyas, Abhay (International Research Journal of Ayurveda & Yoga, 2021)
Shaligram Nighantu is considered last in the series of classical nighantus written by Lala Shaligram Vaishya. Shaligram Nighantu is a combined portion of volumes 7 and 8 of Brihan Nighantu Ratnakar. Lexicons of Ayurveda details an enormous number of vishahar dravyas and their practical utility. According to Shaligram Nighantu, vishahar dravyas may show antihistaminic and immunomodulatory activities. In a similar context, Shaligram Nighantu has elaborated many anti venomous dravyas like Neem (Azadirachta indica A. Juss.), Bakuchi (Psoralea corylifolia L.), Kutki (Picrorrhiza kurroa Royle ex Benth.), etc. This article provides an overall view of Vishahar Dravyas mentioned in Shaligram Nighantu.